System opieki społecznej w okresie Polski Ludowej (lata 1944–1989). Zarys problematyki - Brenk, Mikołaj (Biuletyn Historii Wychowania, 2017)
In the Polish People’s Republic (1944–1989), a number of organisational and ideological changes were made in the social welfare sector: most of the ways of organising help that were tested during the interwar period were replaced with new concepts, often with sad consequences for those in need. This article presents the changes that took place in the Polish social security sector in the decades after World War II. Subsequent attempts to reform the social welfare system have been shown with the use of archival materials, other historical sources and literature on the subject.